Virtual Reality Relaxation for Reducing Perceived Stress of Intensive Care Nurses During the COVID-19 Pandemic - Nijland, J. W. H. Mathijs; Veling, Wim; Lestestuiver, Bart P.; Van Driel, Catheleine M. G. (Frontiers in Psychology, 2021)
During the COVID-19 pandemic ICU nurses endure high levels of stress. VR relaxation (VRelax, containing 360º immersive environments) provides an easy-to-use and effective means to induce positive affect and reduce perceived stress. We investigated feasibility and immediate effect on perceived stress of VRelax use by ICU nurses during work shifts. ICU nurses working with COVID-19 patients in a academic hospital could use VRelax as a ten-minute break during their shift. Primary outcome was the difference between perceived stress immediately before and after VRelax use measured by a single-question VAS-stress scale. Statistical significance difference of the mean VAS-stress before and after use was determined using the paired t student test. A socio-demographic questionnaire, a questionnaire on perceived stress and stress-resilience and VRelax-user-experiences were sent by email. 86 (26%) nurses used VRelax at least once; 77% (N=66) of these filled out the VAS-stress scale before and after use of VRelax. Mean perceived stress lowered with 39.9% after use of VRelax (mean difference = 14.0, SD = 13.3, p <0.005). Mean score on the Perceived stress scale-10 was 11.4 (SD=6.50), mean score on the Connor-Davidson-Resilience Scale-10 was 29.0 (SD=5.51). 62% of the ICU nurses thought VRelax was helpful to reduce stress. Main barrier for use was a high workload. It is feasible for nurses to use VRelax in an ICU context. VRelax is an effective intervention to reduce immediate perceived stress and is of added value in stressful situations as during the COVID-19 pandemic, inducing a positive affective state and lowering perceived stress.